Gotong Royong with Doctor Soetomo to Build Gedung Nasional Indonesia and Nationality Awareness 1924”1938 - Samidi, Samidi (MOZAIK HUMANIORA, 2023)
This article examines the need for national building infrastructure as a means of struggle for the Indonesische Studieclub. Citizen participation, thus, is needed to realize Gedung Nasional Indonesia (GNI) independently since at that time the Dutch East Indies were experiencing an economic recession. Consequently, this decision was seen as a paradox. This article, hence, was focussed on reasons for building a national building during the economic crisis period, funding strategies, as well as the spirit of indigenous people who wanted to be resurrected. In other words, this article aims to explain the synergistic practices of inclusive institutions and indigenous people as well as the efforts of the Indonesische Studieclub to fight for the interests of indigenous peoples. To pursue the aim of this article, historical method was used. Newspaper reports published in the 1920s and 1930s then were used as primary data. The results showed Dr. Soetomo as a leader with the experience and ability to integrate different political and ideological currents could gain the sympathy of the indigenous people indicated with the success of leading the Indonesische Studieclub and Persatuan Bangsa Indonesia (the United Nations of Indonesia) as inclusive institutions. Furthermore, Dr. Soetomo and his organization were able to mobilize citizen participation through gotong royong tradition (Mutual Cooperation) to build a national building in Surabaya. Their spirit of togetherness even was able to create a useful national building as a centre for the struggle of indigenous peoples to strengthen national awareness. In short, gotong royong as social capital could be optimized as a means of fighting for building national awareness.